2002
DOI: 10.1210/er.2001-9002
|View full text |Cite
|
Sign up to set email alerts
|

IX: Summary of Meta-Analyses of Therapies for Postmenopausal Osteoporosis

Abstract: This section summarizes the results of the seven systematic reviews of osteoporosis therapies published in this series [calcium, vitamin D, hormone replacement therapy (HRT), alendronate, risedronate, raloxifene, and calcitonin] and systematic reviews of etidronate and fluoride we have published elsewhere. We highlight the methodological strengths and weaknesses of the individual studies, and summarize the effects of treatments on the risk of vertebral and nonvertebral fractures and on bone density, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
229
3
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(246 citation statements)
references
References 30 publications
6
229
3
8
Order By: Relevance
“…The efficacy of a bisphosphonate (an anti-resorptive drug), risedronate, for postmenopausal osteoporosis has been established: risedronate reduces the incidence of vertebral and nonvertebral fractures in postmenopausal women with osteoporosis [3]. Recently, however, it has been reported that suppressed bone turnover by long-term treatment with high-dose risedronate increased microdamage accumulation in the dog rib [11], suggesting long-term and/or high-dose risedronate treatment may deteriorate bone quality through microdamage accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of a bisphosphonate (an anti-resorptive drug), risedronate, for postmenopausal osteoporosis has been established: risedronate reduces the incidence of vertebral and nonvertebral fractures in postmenopausal women with osteoporosis [3]. Recently, however, it has been reported that suppressed bone turnover by long-term treatment with high-dose risedronate increased microdamage accumulation in the dog rib [11], suggesting long-term and/or high-dose risedronate treatment may deteriorate bone quality through microdamage accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In turn, their effects on the reduction of non-vertebral fractures, including hip, is quite variable. [4][5][6] Until recently, the evaluation of drug effects on trabecular and cortical bone microarchitecture was made by histomorphometric analysis and micro-computed tomography of bone biopsy specimen. 7 Although dynamic histomophometric analysis of iliac crest bone biopsies is still necessary to assess bone mineral apposition rate and cellular activities, 8 the development of high-resolution peripheral quantitative computed tomography (HR-pQCT) allows non-invasive assessment of volumetric density and some parameters of bone microstructure at peripheral sites in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…However, BMD has demonstrated limitations for predicting bone fracture and understanding the roles of estrogen in bone quality, formation and resorption. [3][4][5] In particular, BMD is unable to assess changes in Type I collagen structure that are keys to understanding bone toughness. The structural changes that occur in Type I collagen matrix under conditions of estrogen depletion and drug treatment remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%